KAPASITAS REPRODUKSI PARASITOID TELUR Trichogrammatoidea nana Zehntner (Hymenoptera:Trichogrammatidae) - - Sujak; Dwi Adi Sunarto (Agrovigor, 2011)
Trichogramma nana is one species of egg parasitoids that are polifag. insect pests that attack crops such as soybean pod borer and rice. Research conducted at the Laboratory of Entomology Research Institute for Tobacco and Fiber Crops Malang in March until June 2009 that aims to determine the reproductive capacity of T. nana on eggs  C. cephalonica. Reproductive capacity of T. nana allegedly using the net reproductive rate (Ro), estimatedtime of one generation (T), the capacity of population growth (r), and the rate of parasitoids per day (λ). T. nana were tested  came from the rice stem borer  eggs collected from the land in the district of East Java Beji Pasuruan. Eggs C.cephalonica which is used as the host is the result of breeding in the laboratory of Entomology Research Institute for Tobacco and Fiber Crops. The results showed that T. nana has greatpotential  as  biological agents.  Most  female  progeny  produced by adult females aged 1-2 days . On the first day produced 12 and 8 tails on the second day or 40% and 27% of the total of 30 females produced by a female during life.  Reproductive capacity of  T. nana on eggs C. cephalonica the net reproductive rate  Ro) = 44.7, Capacity of population growth (r) = 1.78,  parasitoid growth rate per day (λ)=5.9, and mean - mean length of generation (T) = 10, 9 days.